2021
DOI: 10.1097/ccm.0000000000004876
|View full text |Cite
|
Sign up to set email alerts
|

Choosing Wisely For Critical Care: The Next Five

Abstract: OBJECTIVES: To formulate new “Choosing Wisely” for Critical Care recommendations that identify best practices to avoid waste and promote value while providing critical care. DATA SOURCES: Semistructured narrative literature review and quantitative survey assessments. STUDY SELECTION: English language publications that examined critical care practices in relation to reducing cost or waste. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 60 publications
0
27
0
4
Order By: Relevance
“…The standardized mortality ratio (SMR), using the prediction of mortality from the score of the SAPS-3 score, was 1.25 (if we consider the hospital mortality of the patient admitted to the ICU, we have an SMR of 1.3). The time (in days) elapsed between the onset of symptoms and hospitalization and the time to perform tracheotomy between our patients and patients transferred from another institution for continuity of care in our ICU did not show a significant difference (9 [7][8][9][10][11][12] vs. 9.5 [6.75-12]; p=0.705 and 22 [18][19][20][21][22][23][24][25][26][27] vs. 23 [19][20][21][22][23][24][25][26][27]; p=0.923, respectively). As for invasive ventilatory support, we observed that when we stratified patients by age (over and under 60 years), mortality was found to be 81.1 and 51.4%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The standardized mortality ratio (SMR), using the prediction of mortality from the score of the SAPS-3 score, was 1.25 (if we consider the hospital mortality of the patient admitted to the ICU, we have an SMR of 1.3). The time (in days) elapsed between the onset of symptoms and hospitalization and the time to perform tracheotomy between our patients and patients transferred from another institution for continuity of care in our ICU did not show a significant difference (9 [7][8][9][10][11][12] vs. 9.5 [6.75-12]; p=0.705 and 22 [18][19][20][21][22][23][24][25][26][27] vs. 23 [19][20][21][22][23][24][25][26][27]; p=0.923, respectively). As for invasive ventilatory support, we observed that when we stratified patients by age (over and under 60 years), mortality was found to be 81.1 and 51.4%.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the pandemic caused by SARS-CoV-2 and unlike other hospitals in the city, we set up an inexperienced medical group of nonspecialists in intensive care medicine. To this end, we review our protocols and guide decisions within the recommendations of "choosing wisely" [8][9][10] , in addition to highlighting medical leadership specialized in intensive care medicine and aligned with these recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…In pediatric patients, a careful risk-benefit-analysis has to be performed. While mechanical ventilation is a vital part of critical care medicine, prolonged use brings with it risks such as need for deeper sedation, followed by hemodynamic instability, immobilization and infection, in turn leading back to a prolonged mechanical ventilation and length of PICU-stay ( 45 47 ).…”
Section: Resultsmentioning
confidence: 99%
“…During the pandemic, we were much more selective in testing for patients with COVID-19 to minimize risk to our nurses, porters, radiologists, technicians, and other health-care workers. The concept is not new and is consistent with the values of Choosing Wisely, 10 , 11 , 12 , 13 , 14 but COVID-19 provided an opportunity to consider more carefully how results of testing might influence pretest probabilities and to ponder carefully the usefulness of all testing in critically ill patients.…”
Section: Bram Rochwerg MD Hamilton On Canadamentioning
confidence: 91%